Women and Dirty Money: How Women are Affected by, Involved, and Counter Money Laundering - Kartini Laras Makmur (Jurnal Hukum Prasada, 2022)
Money laundering is a growing threat to global and Indonesian national development. Similar independent research has been minimal and has resulted in gender facets of development in general without determining to what extent women are undermined by, involved, as well as counter money laundering. This research discusses on how women can engage in the fight against money laundering, how money laundering specifically undermine women and what about the involvement of women in money laundering offense. The objective of this research is to promote women empowerment and integrate gender perspectives in improving anti-money laundering actions. The principal approach of this research is analytical descriptive using document and content analysis to observe the gendered aspect of money laundering. In this way, the findings may contribute to strengthening women’s engagement in anti-money laundering efforts. The result of this study shows that the involvement of women in anti-money laundering can strengthen prevention attempts, foster trust, and improve community outreach. This role is due to the money laundering specific consequence for women such as the decrease of public revenue available for gender equality services and programs. In addition, since women are less likely to tolerate tax evasion and money laundering, the more women in law enforcement, especially in decision-making roles and consideration to gender-sensitive responses make policing in anti-money laundering more effective.